Frenectomy with anterior lingual sulcoplasty for an implant-supported overdenture: A clinical report - Perri De Carvalho, Paulo Sergio; Janjacomo, Luiz Antonio [UNESP]; Ponzoni, Daniela [UNESP] (Elsevier, 2016)
This clinical report describes the deepening of a patient's anterior mandibular lingual sulcus in combination with frenectomy and the use of an acrylic resin guiding device fixed to an osseointegrated dental implant to maintain the patency of the new sulcular depth.